الحديث الشريف وموقف المستشرقين في حجته - Muhammad Izan Bin Mohamad Taslim (Kolej Universiti Islam Malaysia, 2011)
This research discusses the attitude of the Orientalists towards the authority of the sunnah. The method used is primarily based on library research and reference to books related to the topic, includes the exposition of some of the accusations made by the Orientalists relating to the sanad and matan of a hadith, as well as the counter arguments given by the Muslim scholars to prove the authenticity of both the sanad and matan. It is found that the sunnah is indeed the second authentic source of Islam and all the confusions liaised by the Orientalists in it aye all baseless and meant to turn Muslims away from its teachings. As such, the contributions of Muslim scholars in this matter are vital to ensure the preservation of sunnah for the present and future generations.